Sex-biased dispersal in a northern ungulate population - Haanes, Hallvard; Røed, Knut H.; Rosef, Olav (Rangifer, 2011)
In most mammals dispersal is male-biased and in many polygynous ungulates female philopatry and matrilineal grouping involve small-scale genetic structure. We have through sex-related differences in microsatellite allele distribution addressed sex-biased dispersal in a spatially expanding northern ungulate population. The Norwegian red deer population (Cervus elaphus atlanticus) has the last hundred years grown substantially and expanded spatially after a major decline from 300 to 100 years ago. Previous Bayesian analyses suggest a present division of genetic variation into five geographically separated subpopulations. Among these subpopulations the overall Fst values were 0.067 (SE=0.014) for males and 0.094 (SE=0.017) for females. Pairwise Fst values were significantly higher for females than males, demonstrating a stronger genetic structure among females, and that dispersal has been lower in females than males. Accordingly, a higher number of male than female first generation dispersers were identified among the five subpopulations using Bayesian assignment with prior population information, but significantly so only with relaxed stringency levels of assignment. The identified male-biased dispersal distances varied from 30 to 300 kilometers suggesting male biased dispersal on a large scale in red deer.
Keywords: Bayesian assignment; Cervus elaphus; Norwegian deer; range expansion; sex-biased dispersal